Pembagian Hukum Waris Pelaksanaan Hukum Mawaris Di Desa Perdopo Menurut Perspektif Islam: Pelaksanaan Hukum Waris - Nela Dwi Kusumawati; Ashif Az Zafi (TAFAQQUH: Jurnal Hukum Ekonomi Syariah Dan Ahwal Syahsiyah, 2020)
Mawaris law is still used in midst of community life. The implementation of mawaris law in Indonesia is based on customary law and islamic law. Islamic law is used because the majority of the population in Indonesia is moslem, while customary law is used because the plurality of various region and another differs according to customary law in force in the community. One of them is in Perdopo village, Gunung Wungkal district, Pati regency, Central Java province. There are two forms of implementation of mawaris law in the village of Perdopo, namely the distribution of inheritance based on customary law and the distribution of inheritance based on islamic law. If in the implementation of the mawaris law conflict occurs then reconciliation is held. Local religious leaders consider that reconciliation is also justified in islamic sharia, because inheritance is still included in matters relating to muamalah whose implementation is left to the people, provided that in the case there is no dispute. In this case the implementation of the distribution of inheritance is based on what was agreed by the relevant parties and carried out for mutual benefit.